KRISTAL HEMOGLOBIN PADA BERCAK DARAH YANG TERPAPAR BEBERAPA DETERJEN CAIR MELALUI TES TEICHMANN DAN TES TAKAYAMA - Pratiwi, Nurfi; Asni, Enikarmila; Indrayana, Mohammad Tegar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBloodstain were could be found on a lot of form of violence. Bloodstain atthe crime scene often cleaned by the offender to cover the crime. One of thecleaning agents that might be used by the offender is liquid detergent. Thebloodstain that has been contaminated by liquid detergent could give a differentrepresentation on the forensic bloodstain examination. This study was conductedto determine the formation of hemoglobin crystal on contaminated bloodstain bysome liquid detergents using Teichmann and Takayama test. Each driedbloodstains over the slides were flowed by liquid detergent solutions, thenexamined if the hemoglobin cystal were formed or not. In this study, there were atotal of 28 slides were studied and obtained positive results in all slides (100%)through Teichmann or Takayama test. The results of this study showed thathemoglobin crystals can still be found in the bloodstain that had beencontaminated by liquid detergent through Teichmann and Takayama test.Therefore, the conclusion of this study is liquid detergents that used can not affectthe formation of hemoglobin crystal using Teichmann and Takayama tests..Kata kunci: bloodstain, hemoglobin crystal, liquid detergent, Teichmann,Takayama